Activating an evidence-based identity increases the impact of evidence on policymaker beliefs about local climate policies. (14th March 2023) - Hirsch, K C Payne; Wong-Parodi, Gabrielle
Abstract: Evidence-based policymaking has the potential to improve the efficiency and impact of climate mitigation and adaptation policies, but that promise cannot be fulfilled if policymakers fail to change their minds (update their beliefs) when presented with new evidence. Research suggests that individuals often resist changing their mind, especially on polarized topics like climate action. Here we explore whether an 'evidence-based policymaker' intervention can reduce resistance when policymakers interpret new information. We hypothesize that, if policymakers wish to see themselves as 'evidence-based', reminding them of that identity can make changing their beliefs more comfortable. This is because belief-updating provides an opportunity to affirm their identity as an evidence-based policymaker. In two survey studies of state and local U.S. policymakers—a neutral policy pilot ( n = 152) and a polarizing climate policy experiment ( n = 356)—we show that the intervention was effective, even when evidence was incompatible with prior policy beliefs or party ideology. This finding suggests that making evidence-based identities salient when presenting new evidence could increase that information's impact on climate policymaking.